GOOD NEWS FOR THE WORLD. - PEIRANO, MARTA (Prospect, 2025)
The article examines how Project Kontinuum, co-founded by Branko Brkic, aims to save the internet from mass surveillance, algorithmic manipulation, and disinformation by creating a global, journalist-driven, no-algorithm news ecosystem. It mentions that Brkic's plan includes a media literacy campaign called "Choose Truth," a syndication network of newsrooms, a social news platform without algorithms, and a climate awareness initiative called Eve of Destruction.